Implementation of Quality Management of Graduates Based on Spiritual Character in the Industrial Revolution 4.0 Era at SMK IT Al Husna Lebong - Rajab Effendi; Idi Warsah; Jumira Warlizasusi (Universitas Bengkulu, 2022)
Education has a very important role to ensure human survival, so it is necessary to make various efforts to improve the quality of graduates in achieving educational goals. The Industrial Revolution Era 4.0 gave birth to socio-cultural issues that caused problems to become increasingly complex, thus requiring proper management. A nation that has a strong character usually grows and develops and is more advanced and prosperous. So it is important that people with character values in themselves make assets for themselves in the future and assets to advance the nation. This study aims to describe and analyze in depth the implementation of quality management of graduates based on spiritual characters, especially at SMKIT AL Husna Lebong as an Islamic educational institution that has shown a commitment to improving the quality of graduates in the era of the industrial revolution 4.0. This study uses a qualitative approach. Sources of data were obtained from the management of the Anak Soleh Mandiri Foundation (ASMA) Curup, the Education Division of the ASMA Curup foundation, the principal and vice principal of SMKIT AL Husna Lebong and students. Data collection techniques are observation, interviews, documentation studies and data analysis using the Milles and Huberman models. The results of this study indicate that the implementation of graduate quality management in strategic planning of Islamic education at SMKIT AL Husna through a JSIT-based program strategy by instilling ukhrowi values in every learning process through the POSDCORB management pattern (Planing, Organizing, Staffing, Directing, Coordinating, Reporting and Budgeting ) as the effectiveness of implementing quality management for graduates with character.